Targeting tumor metabolism through precision nutrition: A therapeutic strategy to improve cancer outcomes - Debdeep Chattopadhyay; Anushka Saha; Durva Tendulkar; Trisha Banerjee; Souvik Roy; Lopamudra Choudhury; Ramya Lakshmi Rajendran; Prakash Gangadaran; Byeong-Cheol Ahn (World Journal of Clinical Oncology, 2026)
Modern cancer therapies include chemotherapy, immunotherapy, radiation therapy, hormone therapy and newer methods like oncolytic viruses and chimeric antigen receptor T-cell therapy. These therapies are commonly used to manage cancer, but many patients face serious side effects such as cachexia and treatment related anorexia which can lead to a lower quality of life and a reduced ability to tolerate treatment. This review explores nutrition-based approaches that might help reduce these side effects and improve the effectiveness of these therapies. Dietary modulations like ketogenic diets, fasting mimicking diets and changes in macronutrient intake have shown promise in early studies and preclinical research. These approaches may interact with how tumors use energy and help patients better handle their treatment. However, the exact impact of these strategies on cancer therapy outcomes remains unclear and needs more research through well designed, large scale clinical trials. The review also examines dietary factors that could lower the risk of developing cancer, and it looks at how processed foods and alcohol increase cancer risk as well as how plant-based diets and certain micronutrients may help prevent cancer. These factors might reduce cancer risk by lowering oxidative stress, reducing chronic inflammation, altering gut bacteria and changing gene expression. Additionally, strategies tailored to specific stages of cancer treatment including assessing and optimizing nutritional needs pre-treatment providing supportive nutrition during treatment for conditions like mucositis and malnutrition and managing recovery has also been discussed. New experimental technologies such as nanoparticles like cargos, CRISPR-Cas9 and artificial intelligence as a key part of comprehensive cancer care are the key points which has been discussed with the goal of improving treatment results and enhancing the quality of life for cancer survivors.